Impedimetric detection of gut-derived metabolites using 2D Germanene-based materials - Lim, Rachel Rui Xia (2024)
Apart from the extensively researched graphene under the Group 14 2D materials, monolayered germanene and its derivatives have been gaining interest lately as alternative class of 2D materials owing to their facile synthesis, and attractive electronic and optical properties. Herein, three different functionalized germanene-based nanomaterials, namely Ge-H, Ge-CH3 and Ge-C3-CN were investigated on their novel incorporation in impedimetric immunosensors for the detection of gut-derived metabolites associated with neurological diseases, such as kynurenic acid (KA) and quinolinic acid (QA). The designed germanene-based immunosensor relies on an indirect competitive mechanism using disposable electrode printed chips. The competition for a fixed binding site of a primary antibody occurs between the bovine serum albumin-conjugated antigens on the electrode surface and the free antigens in the solution. Among the three materials, Ge-H displayed superior bioanalytical performance in KA and QA detection. Lower limits of detection of 5.07-11.38 ng/mL (26.79-68.11 nM) were attained for KA and QA with a faster reaction time than previously reported methods. Also, minimal cross-reactivity with interfering compounds, good reproducibility in impedimetric responses (RSD = 2.43-7.51 %) and long-term stability up to a month at 4 °C were the other attributes that the proposed Ge-H competitive impedimetric immunosensor has accomplished. The application of the developed Ge-H immunosensor to serum samples allowed an accurate KA and QA quantification at physiologically relevant levels. This work serves as a stepping-stone in the development of germanene-based nanomaterials for their implementation into cost-effective, miniaturized, portable and rapid impedimetric immunosensors, which are highly desirable for point-of-care testing in clinical settings.